Hybrid Performance as The Behavior of Singing Folk Songs Chorally in Indonesia Choir Competition in 2019 - Rachel Mediana Untung; Wisma Nugraha Christianto; Victor Ganap (Jurnal Kawistara, 2022)
The artistic contestation between choral culture and folk song is an important concern in the study of musicology. The problem that is of concern in this study focuses on singing behavior in singing hybrid vocal music. Choir singing behavior has standard vocal techniques, on the other hand the context of understanding folk songs includes natural singing expressions from an ethnicity without being overshadowed by good vocal techniques. The study aims to reconstruct the practice of artistic requirements in Indonesian folksong choir competitions. The study is important because there is artistic contestation between choir culture and folk songs culture leading to a good hybrid performance in the Folklore category. This research method takes material from singing events through observations and studies of audio-visual documentation that are observed repeatedly. This study uses a performance centered approach study that concentrates on the choir's performance. Descriptive-analytic analysis is used as a consequence of the material of the event‘s  that relies on careful descriptions. The results of this study indicate, firstly the choirs which sang folk song repertoire are a hybrid performance characteristic.  Second, the relationship that occurs between artistic requirement and the reality of performances on stage occurs in a multidimensional manner. It was found that there was an adjustment to standardization in the perspective of the coral setting. Third, an understanding of the performance practice as multidimentional and hybrid with artistic requirements shows that a small portion is given to other dimensions (kinesthetic & visual).The findings can be used to reformulate artistic requirements entailing a bigger cultural aspect of folk songs.